Analisis nilai moral dalam cerita rakyat Saridin yang sakti di Pati - Suprapti, Suprapti; Kanzunuddin, Moh.; Fathurohman, Irfa’I (Trihayu: Jurnal Pendidikan Ke-SD-an, 2025)
This research aims to identify and analyze the moral values ​​contained in the folklore "Saridin the Sakti" from the East Coast of Pati, as well as understanding its meaning, function and implications for character education at the elementary school level. The research approach was descriptive qualitative with content analysis methods, research data was obtained from the written text of the story "Saridin the Sakti". The research results show that the story of Saridin Yang Sakti has moral values ​​including: sincerity, patience, honesty, obedience, responsibility, and lessons about humility. These values ​​function as a socio-cultural ethical guide in Pati society, teaching about the consequences of actions and the importance of spiritual guidance. The results of the research show that the magical Saridin story has very strong moral values. Regarding the implications of this research, it is very relevant as teaching material for character education for elementary school students. Therefore, practically the results of this research can be a reference in the world of education for developing learning modules based on local wisdom values.